Division of the genus Chryseobacterium: Observation of discontinuities in amino acid identity values, a possible consequence of major extinction events, guides transfer of nine species to the genus Epilithonimonas, eleven species to the genus Kaistella, and three species to the genus Halpernia gen. nov., with description of Kaistella daneshvariae sp. nov. and Epilithonimonas vandammei sp. nov. derived from clinical specimens. Issue 8 (2nd August 2020) - Nicholson, Ainsley C.; Gulvik, Christopher A.; Whitney, Anne M.; Humrighouse, Ben W.; Bell, Melissa E.; Holmes, Barry; Steigerwalt, Arnie G.; Villarma, Aaron; Sheth, Mili; Batra, Dhwani; Rowe, Lori A.; Burroughs, Mark; et al.
Abstract : The genus Chryseobacterium in the family Weeksellaceae is known to be polyphyletic. Amino acid identity (AAI) values were calculated from whole-genome sequences of species of the genus Chryseobacterium, and their distribution was found to be multi-modal. These naturally-occurring non-continuities were leveraged to standardise genus assignment of these species. We speculate that this multi-modal distribution is a consequence of loss of biodiversity during major extinction events, leading to the concept that a bacterial genus corresponds to a set of species that diversified since the Permian extinction. Transfer of nine species ( Chryseobacterium arachidiradicis, Chryseobacterium bovis, Chryseobacterium caeni, Chryseobacterium hispanicum, Chryseobacterium hominis, Chryseobacterium hungaricum ﻿, , Chryseobacterium pallidum and Chryseobacterium zeae ) to the genus Epilithonimonas and eleven ( Chryseobacterium anthropi, Chryseobacterium antarcticum, Chryseobacterium carnis, Chryseobacterium chaponense, Chryseobacterium haifense, Chryseobacterium jeonii, Chryseobacterium montanum, Chryseobacterium palustre, Chryseobacterium solincola, Chryseobacterium treverense and Chryseobacterium yonginense ) to the genus Kaistella is proposed. Two novel species are described: Kaistella daneshvariae sp. nov. and Epilithonimonas vandammei sp. nov. Evidence is presented to support the assignment of Planobacterium taklimakanense to a genus apart from Chryseobacterium, to which Planobacterium salipaludis comb nov. also belongs. The novel genus Halpernia is proposed, to contain the type species Halpernia frigidisoli comb. nov., along with Halpernia humi comb. nov., and Halpernia marina comb. nov.